2009
DOI: 10.1080/15287390902841003
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis ofMSH6Gene Mutation Frequency in Colorectal and Endometrial Cancers

Abstract: Studies on mutations and mutation frequencies of the MSH6 gene, which mainly focus on new types of mutations in small samples, have been published ever since the first report of MSH6 mutation in two atypical hereditary non-polyposis colorectal cancer patients. However, the results remain inconsistent. Therefore, a systematic review was conducted and a meta-analysis was undertaken to determine the frequency of MSH6 mutation in colorectal and endometrial cancers. From 27 studies, 180 cases with MSH6 mutation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
(32 reference statements)
3
10
0
Order By: Relevance
“…The carrier shows a late-onset endometrial cancer with the absence of any staining of the MSH6 protein and MSS tumor. Similar results have been reported in several studies (19). The higher rate of mutations in this study appears in the MSH2 gene (nearly double that in MLH1); this is probably because of the high number of recurrent mutations in this gene.…”
Section: Discussionsupporting
confidence: 92%
“…The carrier shows a late-onset endometrial cancer with the absence of any staining of the MSH6 protein and MSS tumor. Similar results have been reported in several studies (19). The higher rate of mutations in this study appears in the MSH2 gene (nearly double that in MLH1); this is probably because of the high number of recurrent mutations in this gene.…”
Section: Discussionsupporting
confidence: 92%
“…6) in the present study. Previous studies from Western countries reported that mean age at the diagnosis of endometrial cancer was ~48 years in MLH1 or MSH2 mutation carriers (9,30,31) and 56.5 years in MSH6 mutation carriers (32). Thus, the endometrial carcinoma in MSH6 mutation carriers was generally diagnosed at an older age (~5 years later) Table IV.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, MSI testing for all CRC cases would be a useful screening method for high-risk individuals with an MSH6 mutation. However, some MSH6 mutation carriers developed MSI-L or MSS tumors (32). While, an IHC analysis is another potential screening strategy for LS, a recent study reported that ~30% of colon tumors in carriers of pathogenic MSH6 mutations still showed MSH6 protein expression (33).…”
Section: Polyphen-2 C -----------------------------------------------mentioning
confidence: 99%
“…Lynch syndrome is defined by the presence of a germline mutation in one of the mismatch repair genes [Boland, 2005]. Although the majority of these mutations occur in either MLH1 or MSH2, the contribution of mutations in MSH6 or PMS2 (MIM] 600259) is not insignificant [Truninger et al, 2005;Zhao et al, 2009].…”
Section: Introductionmentioning
confidence: 99%